2016
DOI: 10.1021/acs.orglett.6b01298
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Intermolecular C–H Functionalization of Allylic and Benzylic sp3 C–H Bonds Using N-Sulfonyl-1,2,3-triazoles

Abstract: The enantioselective intermolecular sp3 C–H functionalization at allylic and benzylic positions was achieved using rhodium-catalyzed reactions with 4-phenyl-N-methanesulfonyl-1,2,3-triazole. The optimum dirhodium tetracarboxylate catalyst for these reactions was Rh2(S-NTTL)4. The rhodium-bound α-imino carbene intermediates preferentially reacted with tertiary over primary C–H bonds in good yields and moderate levels of enantioselectivity (66-82% ee). This work demonstrates that N-sulfonyltriazoles can be appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Nevertheless, the catalytic enantioselective version of this tandem process remains elusive. This is in sharp contrast with chiral Rh II catalyst‐mediated highly enantioselective cyclopropanation, C−H insertion,, and formal [3+2] cycloaddition, of 1,2,3‐triazoles. Mechanistically, as described by Miura, Murakami and co‐workers, O ‐insertion of allyl alcohol derivatives to Rh II ‐bound imino carbene intermediates I furnishes zwitterionic intermediate II .…”
Section: Methodsmentioning
confidence: 96%
“…Nevertheless, the catalytic enantioselective version of this tandem process remains elusive. This is in sharp contrast with chiral Rh II catalyst‐mediated highly enantioselective cyclopropanation, C−H insertion,, and formal [3+2] cycloaddition, of 1,2,3‐triazoles. Mechanistically, as described by Miura, Murakami and co‐workers, O ‐insertion of allyl alcohol derivatives to Rh II ‐bound imino carbene intermediates I furnishes zwitterionic intermediate II .…”
Section: Methodsmentioning
confidence: 96%
“…7779 Around the same time as Müller’s initial report of an acceptor/acceptor-substituted carbenoid for moderately enantioselective allylic C–H alkylations, Davies began to explore this mode of C–H functionalization with donor/acceptor stabilized carbenoids. 8085 These reports on the Rh 2 (DOSP) 4 -catalyzed decomposition of aryldiazoacetates have become one of the most selective methods for C(sp 3 )–H functionalization.…”
Section: Enantioselective Allylic Alkylation Of Unactivated Alkenesmentioning
confidence: 99%
“…Davies et al. reported that the reaction of 4‐phenyltriazole with 5 e , using Rh 2 ( S ‐NTTL) 4 as the catalyst, (1.0 mol %) gave the C(sp 3 )−H insertion product (24 %, 72 % ee ) and a [3+2] cycloadduct (10 %, 92 % ee ; Scheme a) . In contrast, when the reaction conditions A were applied to 4 a , the N ‐sulfonylenaminones 11 ae and 12 ae were obtained in 69 and 19 % yields, respectively (Scheme b).…”
Section: Figurementioning
confidence: 99%